Feasibility of Formal Mindfulness-Based Stress-Resilience Training Among Surgery Interns: A Randomized Clinical Trial - Lebares, Carter C. (JAMA Surg, 2018)
IMPORTANCE: Among surgical trainees, burnout and distress are prevalent, but mindfulness has been shown to decrease the risk of depression, suicidal ideation, burnout, and overwhelming stress. In other high-stress populations, formal mindfulness training has been shown to improve mental health, yet this approach has not been tried in surgery. OBJECTIVE: To test the feasibility and acceptability of modified Mindfulness-Based Stress Reduction (MBSR) training during surgical residency. DESIGN, SETTING, AND PARTICIPANTS: A pilot randomized clinical trial of modified MBSR vs an active control was conducted with 21 surgical interns in a residency training program at a tertiary academic medical center, from April 30, 2016, to December 2017. INTERVENTIONS: Weekly 2-hour, modified MBSR classes and 20 minutes of suggested daily home practice over an 8-week period. MAIN OUTCOMES AND MEASURES: Feasibility was assessed along 6 domains (demand, implementation, practicality, acceptability, adaptation, and integration), using focus groups, interviews, surveys, attendance, daily practice time, and subjective self-report of experience. RESULTS: Of the 21 residents included in the analysis, 13 were men (62%). Mean (SD [range]) age of the intervention group was 29.0 (2.4 [24-31]) years, and the mean (SD [range]) age of the control group was 27.4 (2.1 [27-33]) years. Formal stress-resilience training was feasible through cultivation of stakeholder support. Modified MBSR was acceptable as evidenced by no attrition; high attendance (12 of 96 absences [13%] in the intervention group and 11 of 72 absences [15%] in the control group); no significant difference in days per week practiced between groups; similar mean (SD) daily practice time between groups with significant differences only in week 1 (control, 28.15 [12.55] minutes; intervention, 15.47 [4.06] minutes; P = .02), week 2 (control, 23.89 [12.93] minutes; intervention, 12.61 [6.06] minutes; P = .03), and week 4 (control, 26.26 [13.12] minutes; intervention, 15.36 [6.13] minutes; P = .04); course satisfaction (based on interviews and focus group feedback); and posttraining-perceived credibility (control, 18.00 [4.24]; intervention, 20.00 [6.55]; P = .03). Mindfulness skills were integrated into personal and professional settings and the independent practice of mindfulness skills continued over 12 months of follow-up (mean days [SD] per week formal practice, 3 [1.0]). CONCLUSIONS AND RELEVANCE: Formal MBSR training is feasible and acceptable to surgical interns at a tertiary academic center. Interns found the concepts and skills useful both personally and professionally and participation had no detrimental effect on their surgical training or patient care. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT03141190